Conductividad, oxígeno disuelto, PH y temperatura en el rio bermudez (Costa Rica) y su relación con el uso del suelo en la cuenca (ING) - Castro, Leda (1996)
Temporal and spatial variation in conductivity, dissolved oxygen, pH and temperature were monitored in the Bermúdez River, in the Central Valley, Costa Rica, during 28 months.  Most of the watershed is occupied by intensively-managed coffee plantations (53%) followed by urban areas (30%). Water is of acceptable quality in the upper part of basin, where forests and pastures predominate but gradually deteriorates until it becomes useless for almost all human activities. Conductivity, dissolved oxygen and pH show a temporal variation associated with fluctuations in precipitation and with the intensity of the contribution of waste waters.The situation in the Bermúdez River may be considered as representative of what is occurring in other rivers in the Central Valley. Although an institutional policy to prevent organic pollution from coffee processing plants has been implemented recently, other pollution sources remain. Water from this river is currently used for irrigation of several agricultural fields in the lowlands, a fact that represents a serious human health risk. An integrated river basin management strategy is necessary.